(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article aims to explore the challenges and opportunities for gender equality and women’s empowerment within the social and solidarity economy. It will examine the various barriers that hinder women’s full participation in SSE and highlight innovative practices and strategies that have been successful in promoting gender equality. Additionally, the article will analyze the role of governments, civil society organizations, and international institutions in advancing women’s economic empowerment in SSE. By shedding light on these issues, the article seeks to contribute to the ongoing discourse on gender equality and SSE and provide insights for policymakers, practitioners, and researchers working in this field